Diets supplemented with condensed and hydrolysable tannins affected rumen fatty acid profile and plasmalogen lipids, ammonia and methane production in an in vitro study. Issue 1 (1st January 2021) - Cappucci, Alice; Mantino, Alberto; Buccioni, Arianna; Casarosa, Laura; Conte, Giuseppe; Serra, Andrea; Mannelli, Federica; Luciano, Giuseppe; Foggi, Giulia; Mele, Marcello
Abstract: The livestock sector constitutes 14.5% of global green-house gas (GHG) emissions and soil and water pollution due to nitrogen excretion. Methane and nitrogen excretions in ruminants can be mitigated by specific feeding strategies, and tannins reduce methanogenesis and ammonia syntheses. In our study, two kinds of condensed tannins (Mimosa and Gambier) and two kinds of hydrolysable tannins (Chestnut and Tara) were added (4 g/100 g DM) to a basal feed (barley: 48 g/100 g DM, wheat bran: 23 g/100 g DM, dehydrated alfalfa hay:15 g/100 g DM, soybean meal: 10 g/100 g DM and molasses: 2 g/100 g DM), inoculated with rumen fluid and fermented for 24 h. The methane, ammonia, fatty acid and plasmalogen lipid profile were determined. The results confirmed that tannins are an important family of heterogeneous compounds whose effect on rumen metabolism is strongly linked to their different characteristics. Chestnut tannin extract was shown to be a good compromise. It improved the sustainability of ruminant rearing by decreasing methanogenesis (control feed 0.159 vs chestnut feed 0.137 mmol/L rumen fluid; p  = .0326), ammonia production (control feed 248 vs chestnut feed 179 mg/L rumen fluid; p  < .0001) and enhancing acetate synthesis (production rate: chestnut 68.68% vs 49.64% of control). HIGHLIGHTS: Tannin extracts from trees and shrubs can be used to modulate rumen fermentation. The positive effect of chestnut tannin extract was demonstrated on methane and ammonia production. Tannins showed no protective action on C18:2 trans 11.